Fast photocatalytic degradation of dyes using low-power laser-fabricated Cu2O–Cu nanocomposites. Issue 36 (4th June 2018) - Li, Shengling; Lin, Qingxia; Liu, Xianhua; Yang, Li; Ding, Jie; Dong, Feng; Li, Yang; Irfan, Muhammad; Zhang, Pingping
Abstract : Facile synthesis of Cu2 O–Cu nanocomposites by using a low-power CO2 laser was realized, and the fabricated nanomaterials showed excellent photocatalytic activity for the degradation of various dyes. Abstract : In this study, we report a simple method to controllably synthesize Cu2 O–Cu nanocomposites by using a low-power CO2 laser, and application of these nanomaterials for photocatalytic degradation of methylene blue (MB). Our experiments demonstrate that efficient tailoring of the Cu2 O–Cu nanocomposites can be realized by accurate control and optimization of the ambient parameters, such as laser energy and NaOH concentration. Compared to hydrothermally fabricated Cu2 O–Cu catalysts, the laser-reduced composites exhibit better visible-light photocatalytic activity for MB degradation, which could be attributed to the formation of special catalytically active structures on the nanocomposite surface. Under the conditions of 10 mA laser irradiation and 5 M NaOH addition, the fabricated Cu2 O–Cu composites had the highest catalytic activity. The degradation rate of MB is 90.10% after visible-light irradiation for 50 min under the optimum conditions. The as-synthesized Cu2 O–Cu composites showed selective dye degradation, and exhibit relatively higher photocatalytic efficiency for positively charged dyes. This work could lead to facile synthesis of high-performance photocatalysts for fast removal of environmentally hazardous dyes from aqueous solution.